Clinical chorioamnionitis and histologic placental inflammation: association with early-neonatal sepsis. (12th December 2022) - Rallis, Dimitrios; Lithoxopoulou, Maria; Pervana, Stavroula; Karagianni, Paraskevi; Hatziioannidis, Ilias; Soubasi, Vasiliki; Tsakalidis, Christos
Abstract: Objective: Chorioamnionitis and fetal inflammatory response syndrome (FIRS) are significant risk factors for early onset sepsis (EOS). Recently, the use "Intrauterine Inflammation or Infection or both" or triple I has been proposed, classifying cases into an isolated maternal fever, suspected triple I, or confirmed chorioamnionitis. Evidence suggests that the association between suspected chorioamnionitis and confirmed histological chorioamnionitis (HCA) is not consistent, as well as the impact of HCA on the development of EOS. We aimed to evaluate the association between suspected chorioamnionitis and HCA, the impact of HCA on EOS, and the effect of antepartum antibiotic prophylaxis on EOS. Methods: We retrospectively reviewed the medical records of all infants admitted to our institution, between 2017 and 2018, with a diagnosis of chorioamnionitis. We recorded the clinical evidence of chorioamnionitis, the histologic report of the placenta, the maternal and neonatal data, the neonatal inflammatory markers including C-reactive protein (CRP), and the incidence of EOS. The impact of antepartum antibiotic prophylaxis on the infants' CRP and EOS was calculated, and the logistic regression model was performed to estimate the association of confirmed HCA with EOS, while controlling for FIRS stage, gestation age, birth weight, maternal fever, foul-smelling amniotic fluid, and prolonged rupture of membranes. Results: During the study period, a total of 266 infants were identified; 81 (30%) infants had a confirmed HCA (HCA-present cases), and 185 (70%) infants were diagnosed with suspected triple I (HCA-absent cases). Antepartum antibiotics had been commenced in a significantly higher proportion in HCA-present cases (46%) in comparison to 14% of HCA-absent cases ( p < .001). HCA-present infants were of significantly lower gestation (31.6 ± 4weeks versus 33.3 ± 4weeks, p = .004), and birth weight (1826 ± 840 g versus 2092 ± 849 g, p = .019), they had a significantly higher rate of clinical symptoms (31% versus 6%, p < .001), and a higher CRP at birth and 24 h (1.4 ± 1.5 mg/dL versus 0.3 ± 0.2 mg/dL, p < .001, and 2.1 ± 2.3 mg/dL versus 0.4 ± 0.6 mg/dL, p < .001, respectively). All HCA-present cases had evidence of FIRS; 43% were stage I, 25% stage II, and 32% were FIRS stage III. A significantly higher proportion of HCA-present infants were diagnosed with EOS (46% as compared to 6%, p < .001). The antepartum antibiotic administration was related to a significantly lower CRP at birth and 24 h only in HCA-present cases, albeit not with any reduction ιn EOS incidence. HCA was significantly associated with EOS (RR 3.18, 95% CI 2.81–5.18, p < .001). After adjusting for perinatal factors, the presence of HCA (OR 7.89, 95% CI 1.19-23.34, p = .032) and an advanced FIRS stage (OR 10.35, 95% CI 4.23–25.32, p < .001) were significantly associated with EOS. Conclusions: Amongst infants with suspected chorioamnionitis, the diagnosis is partially supported by histological confirmation, and that is more prominent in pregnancies of a lower gestation. The presence of HCA and an advanced FIRS stage predispose to an increased risk of EOS after adjusting for other perinatal and neonatal factors. The antepartum prophylaxis against intra-amniotic infection was related to a significantly lower CRP in HCA-present cases.